Method for extracting heavy metal from slurry reactor hydrogenation residual oil
Through a method of extracting heavy metals from hydrogenated residue oil from slurry beds, using biomass filter material and heat treatment technology, the problems of high cost of existing methods and poor removal of multiple metals have been successfully solved, and the slag control is achieved Efficient removal and recycling of vanadium, molybdenum and nickel in oil.
Patent Information
- Application Number
- CN202411545167.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-11
AI Technical Summary
The existing methods of extracting heavy metals from residual oil are costly and have poor removal effects on multiple metals.
A method of extracting heavy metals from slurry bed hydrogenation residues, including mixing and heating the residue with diluent, adding biomass filter material for reduced pressure-heat filtration, followed by roasting, lye leaching and acidic solution treatment In addition, heavy metals such as vanadium, molybdenum and nickel were successfully isolated and recovered from residual oil.
The efficient removal of vanadium, molybdenum and nickel in residual oil was achieved, with the removal rates reaching 94.09%, 86.22% and 85.56% respectively. This method is simple and easy to implement, and does not require complex equipment and special operating skills.
Smart Images

Figure CN119410908A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of heavy metal extraction, in particular to a method for extracting heavy metals from slurry bed hydrogenated residual oil. Background Art
[0002] Residue oil, also known as "bottom of the barrel oil", is the most difficult heavy component in petroleum to utilize. It is enriched with more than 95% of nitrogen, sulfur, nickel, vanadium and other elements in petroleum. Among them, most of the metals are present in asphaltene, which makes subsequent processing very difficult. Nickel and vanadium will corrode equipment during the oil processing process, poison and deactivate catalysts, thereby reducing product quality, affecting the economic benefits of refineries, and even causing production safety accidents. Therefore, exploring methods to remove metals from residue oil is of great practical significance.
[0003] At present, the main methods for removing metals from residual oil are: acid extraction, hydrogenation, chelation separation, ultrasonic method, etc. Acid extraction refers to the use of acidic solvents as extraction solvents to remove metals from heavy oil by extraction, but the acidic solvents used are highly corrosive and will damage the equipment. Improper use will also cause environmental pollution. Hydrodemetallization refers to a demetallization technology in which metals are reduced by hydrogen and adsorbed on the surface of the catalyst to reduce the metal content in the residual oil. Hydrodemetallization has a good removal effect on nickel and vanadium in residual oil, but this technology has strict requirements on equipment quality, needs to be resistant to extreme conditions, and has a high investment cost. Chelation separation refers to the demetallization of metal compounds under the action of external high energy. The metal changes from a combined state to a free state. The chelate reacts with the free metal ions to form a precipitate or a metal compound that is easily dispersed in the water phase. The metal is then removed by oil-water separation, but the chelate has a high cost and poor stability. This method needs to be used in combination with other methods, otherwise the metal removal efficiency is low. The ultrasonic method utilizes the cavitation effect of ultrasound. During this process, ultrasound will form many small bubbles on the solid surface. These bubbles will continue to expand. When they expand to a certain extent, they will stop absorbing energy and collapse instantly, generating high temperature and high pressure. This effect helps to separate heavy metals, but this method consumes a lot of energy, the operating parameters are complex to control, and the treatment effect is limited.
[0004] Although the current methods for removing metals from residual oil have their own advantages, they also have the following disadvantages:
[0005] (1) The effect of removing multiple metals simultaneously is poor;
[0006] (2) Due to the limitations of the equipment used, the best effect cannot be achieved;
[0007] (3) The cost is relatively high.
[0008] Therefore, there is an urgent need for a simple and easy method with good removal effect of multiple metals for extracting heavy metals from residual oil. Summary of the invention
[0009] The purpose of the present invention is to provide a method for extracting heavy metals from slurry bed hydrogenated residual oil, so as to solve the problems of high cost and poor removal effect of multiple metals in the above-mentioned methods for removing metals from residual oil.
[0010] To achieve the above object, the present invention provides a method for extracting heavy metals from slurry bed hydrogenated residue oil, comprising the following steps:
[0011] (1) mixing the residual oil and the diluent and heating and melting them to obtain a mixed residual oil;
[0012] (2) washing, drying and crushing the natural biomass to obtain a biomass filter material;
[0013] (3) mixing and stirring the mixed residual oil and the biomass filter material, and then performing decompression-hot filtration while hot to obtain a filter cake and a first filtrate;
[0014] (4) calcining the filter cake to obtain a sintered product;
[0015] (5) immersing the sintered product in an alkaline solution, and then filtering to obtain an alkaline leaching solution and a filter residue;
[0016] (6) adding an acidic solution 1 to the filter residue to dissolve it, then filtering it to obtain a second filtrate, adding an alkaline solution 2 to the second filtrate to precipitate it, then filtering it to obtain a nickel hydroxide precipitate, and sintering the nickel hydroxide precipitate to obtain a nickel oxide product;
[0017] (7) adding ammonium salt to the alkaline leaching solution to promote the formation of precipitation between ammonium ions and vanadium ions in the alkaline leaching solution, followed by filtering to obtain a vanadium precipitate and a third filtrate, and sintering the vanadium precipitate to obtain a V2O5 product;
[0018] (8) Add acidic solution 2 to the third filtrate to promote MoO4 2- With H + A reaction occurs to generate H2MoO4 precipitate, which is then filtered to obtain molybdenum precipitate, and the molybdenum precipitate is calcined to obtain MoO3 product.
[0019] Preferably, in step (1), the diluent includes one or more of distilled diesel, catalytic diesel, and RDS diesel; the mass ratio of residual oil to diluent is (2-6):1; the heating temperature is 125-135°C, and the heating time is 10-20 min.
[0020] Preferably, the natural biomass is camellia oleifera shell, and the particle size of the biomass filter material is 50-200 meshes.
[0021] Preferably, in step (3), the amount of biomass filter material added is 0.5-4% of the mass of the mixed residual oil, the temperature of mixing and stirring is 100-140° C., and the time is 10-20 min.
[0022] Preferably, in step (4), the calcination temperature is 500-800° C. and the calcination time is 4-10 h.
[0023] More preferably, in step (4), the calcination temperature is 550-600° C. and the calcination time is 5-6 hours.
[0024] Preferably, in step (5), the alkaline solution 1 includes one or more of sodium hydroxide, sodium bicarbonate, sodium carbonate, and potassium hydroxide solution; the concentration of the alkaline solution 1 is 0.5-2 mol / L; the solid-liquid ratio of the sintered product and the alkaline solution 1 is (5-15) mL:1 g; the immersion temperature is 60-100° C., and the time is 60-150 min.
[0025] More preferably, in step (5), the alkaline solution 1 is sodium carbonate; the concentration of the alkaline solution 1 is 1 mol / L; the solid-liquid ratio of the sintered product and the alkaline solution 1 is 10 mL:1 g; the immersion temperature is 80° C. and the time is 120 min.
[0026] Preferably, in step (6), the first acidic solution is hydrochloric acid, the second alkaline solution is sodium hydroxide, the precipitation temperature is 50 to 90° C., and the precipitation time is 1 to 3 hours.
[0027] More preferably, in step (6), the first acidic solution is hydrochloric acid, the second alkaline solution is sodium hydroxide, the precipitation temperature is 60° C., and the time is 2 h.
[0028] Preferably, in step (6), the mass volume ratio of the filter residue to the hydrochloric acid is 10-15 g:1 mL, and sodium hydroxide solution is added to adjust the pH value to 9-11.
[0029] Preferably, in step (6), the sintering temperature of the nickel hydroxide precipitate is 450-550° C., and the sintering time is 1.5-2.5 h.
[0030] Preferably, in step (7), the ammonium salt is an ammonium chloride solution, the precipitation temperature is 50 to 90° C., and the precipitation time is 1 to 3 hours.
[0031] More preferably, in step (7), the ammonium salt is an ammonium chloride solution, the precipitation temperature is 60° C., and the time is 2 h.
[0032] Preferably, in step (7), ammonium salt is added to form a saturated solution, and the sintering temperature of the vanadium precipitate is 450-550° C. and the sintering time is 1.5-2.5 h.
[0033] Preferably, in step (8), the second acidic solution is one or more of sulfuric acid, hydrochloric acid, and nitric acid; the precipitation temperature is 50 to 90° C., and the precipitation time is 1 to 3 hours.
[0034] More preferably, in step (8), the second acidic solution is nitric acid; the precipitation temperature is 60° C., and the precipitation time is 2 h.
[0035] Preferably, in step (8), nitric acid is added to adjust the pH value to 3-4, the sintering temperature of the molybdenum precipitate is 450-550° C., and the sintering time is 1.5-2.5 h.
[0036] Therefore, the present invention adopts a method for extracting heavy metals from slurry bed hydrogenated residual oil with the above structure, which has the following beneficial effects:
[0037] (1) The method of the present invention has a high removal rate for heavy metals vanadium, molybdenum and nickel in residual oil. Under the optimal experimental conditions, the leaching rate of molybdenum is as high as 94.09%, the leaching rate of vanadium is 86.22%, the precipitation rates of molybdenum and vanadium are 93.12% and 81.25% respectively, and the precipitation rate of nickel reaches 85.56%. The present invention can effectively separate and recover these important metal elements from residual oil.
[0038] (2) The method of the present invention includes the steps of decompression-heat extraction, air roasting, alkali solution leaching, etc. These steps are relatively simple, do not require complex equipment or special operating skills, and are easy to implement in industrial production.
[0039] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 is a process flow chart;
[0041] Figure 2 This is the infrared spectrum of slurry bed residue oil;
[0042] Figure 3 This is the infrared spectrum of camellia oleifera shell;
[0043] Figure 4 This is an electron microscope image of the oil-tea camellia shell;
[0044] Figure 5 The appearance of the filter media and filter cake;
[0045] Figure 6 The influence of different diesel fuels on the filtration time and filter cake weight;
[0046] Figure 7 The effect of different diesel fuels on the removal of vanadium, nickel and molybdenum from residual oil;
[0047] Figure 8The influence of different residual oil and diesel mass ratio on filtration time and filter cake weight;
[0048] Fig. 9 The effects of different residue oil and diesel mass ratios on the removal of vanadium, molybdenum and nickel from residue oil;
[0049] Fig.10 The effect of the amount of camellia oleifera shell added on the filtration time and filter cake weight;
[0050] Fig.11 The effect of the amount of camellia oleifera shell added on the removal of vanadium, molybdenum and nickel from the residue oil;
[0051] Fig.12 The effect of filtration temperature on filtration time and filter cake weight;
[0052] Fig.13 The effect of filtration temperature on the removal of vanadium, molybdenum and nickel from residual oil;
[0053] Fig.14 TG and DTG curves of the two filter cakes;
[0054] Fig.15 The effect of calcination time on the burn-out rate of filter cake;
[0055] Fig.16 The effect of roasting time on metal leaching rate;
[0056] Fig.17 The effect of immersion temperature on metal leaching rate;
[0057] Fig.18 The effect of immersion time on metal leaching rate. DETAILED DESCRIPTION
[0058] The present invention will be further described below. It should be noted that this embodiment is based on the technical solution and provides a detailed implementation method and a specific operation process, but the present invention is not limited to this embodiment.
[0059] Example 1
[0060] This embodiment provides a method for extracting heavy metals from slurry bed hydrogenated residual oil, comprising the following steps:
[0061] (1) 80 g of residual oil and 20 g of diluent are mixed and heated to melt to obtain a mixed residual oil;
[0062] The diluent is catalytic diesel; the mass ratio of residual oil to diluent is 4:1; the heating temperature is 130°C and the heating time is 10 minutes;
[0063] (2) washing, drying and crushing the oil tea fruit shell to obtain a biomass filter material, wherein the particle size of the biomass filter material is 100 mesh;
[0064] (3) mixing and stirring the mixed residual oil and the biomass filter material, and then performing decompression-hot filtration while hot to obtain a filter cake and a first filtrate;
[0065] The amount of biomass filter material added was 2% of the mass of the mixed residue oil, the mixing temperature was 130°C, and the time was 10 min;
[0066] (4) calcining the filter cake at a temperature of 550° C. for 6 h to obtain a sintered product;
[0067] (5) immersing the sintered product in an alkaline solution, and then filtering to obtain an alkaline leaching solution and a filter residue;
[0068] The alkaline solution 1 is a sodium carbonate solution; the concentration of the alkaline solution 1 is 1 mol / L; the solid-liquid ratio of the sintered product and the alkaline solution 1 is 10 mL:1 g; the immersion temperature is 80° C. and the immersion time is 120 min;
[0069] (6) adding hydrochloric acid to the filter residue to dissolve it, the addition ratio between the filter residue and the hydrochloric acid is 10:1 (g:mL), then filtering to obtain a second filtrate, adding sodium hydroxide to the second filtrate for precipitation, adjusting the pH value to 10, then filtering to obtain a nickel hydroxide precipitate, and sintering the nickel hydroxide precipitate to obtain a nickel oxide product; the sintering temperature of the nickel hydroxide precipitate is 500°C, and the sintering time is 2h.
[0070] The acid solution 1 is hydrochloric acid, the alkaline solution 2 is sodium hydroxide, the precipitation temperature is 60°C, and the time is 2h;
[0071] (7) adding ammonium salt to the alkaline leaching solution until a saturated solution is formed, thereby promoting the formation of a precipitate between the ammonium ions and the vanadium ions in the alkaline leaching solution, followed by filtering to obtain a vanadium precipitate and a third filtrate, and sintering the vanadium precipitate to obtain a V2O5 product; the sintering temperature of the vanadium precipitate is 500°C, and the sintering time is 2 hours.
[0072] The ammonium salt is ammonium chloride solution, the precipitation temperature is 60°C, and the time is 2h;
[0073] (8) Add nitric acid to the third filtrate to adjust the pH to the range of 3-4, promoting the formation of MoO4 2- With H + A reaction occurs to generate H2MoO4 precipitate, which is then filtered to obtain molybdenum precipitate, and the molybdenum precipitate is calcined to obtain MoO3 product; the sintering temperature of the molybdenum precipitate is 500°C and the sintering time is 2h.
[0074] The second acidic solution is nitric acid; the precipitation temperature is 60°C and the time is 2h.
[0075] Example 2
[0076] The difference between this embodiment and embodiment 1 is that the type of diluent in step (1) is different. In this embodiment, catalytic diesel is replaced by distilled diesel and RDS diesel. Catalytic diesel, distilled diesel and RDS diesel are all purchased from Sinopec Maoming Petrochemical Company.
[0077] Example 3
[0078] The difference between this embodiment and embodiment 1 is that the mass ratio of the residual oil to the diluent in step (1) is different. In this embodiment, the mass ratio of the residual oil to the diluent is replaced by 6:1, 5:1, 3:1, and 2:1.
[0079] Example 4
[0080] The difference between this embodiment and embodiment 1 is that the amount of biomass filter material added in step (3) is different. In this embodiment, 2% is replaced by 0, 1%, 3%, and 4%.
[0081] Example 5
[0082] The difference between this embodiment and embodiment 1 is that the mixing and stirring temperature in step (3) is different. In this embodiment, 130°C is replaced by 100°C, 110°C, 120°C, and 140°C.
[0083] Example 6
[0084] The difference between this embodiment and embodiment 1 is that the calcination time in step (4) is different. In this embodiment, 6 h is replaced by 2 h, 4 h, 8 h and 10 h.
[0085] Example 7
[0086] The difference between this embodiment and embodiment 1 is that the immersion temperature in step (5) is different. In this embodiment, 80°C is replaced by 50°C, 60°C, 70°C and 90°C.
[0087] Example 8
[0088] The difference between this embodiment and embodiment 1 is that the immersion time in step (5) is different. In this embodiment, 120 min is replaced by 30 min, 60 min, 90 min and 150 min.
[0089] Test Example 1
[0090] (1) Characterization of the basic properties of slurry bed residue
[0091] ① Density and kinematic viscosity
[0092] According to the density determination procedure (GB / T 2540-1988), the density of slurry bed residue was measured at 20°C to be 1080.1 kg·m -3According to the kinematic viscosity measurement procedure (GB / T 11137-1989), at 150°C, the kinematic viscosity of the slurry bed residue was measured to be 72.2 mPa·S.
[0093] The results show that the slurry bed residue has the characteristics of high density and high viscosity, and it can be preliminarily judged that it contains a large amount of aromatic components, colloids, and asphaltene components. In view of its high viscosity, diluents are added to reduce its viscosity, which is convenient for hot extraction filtration experiment operation and improves experimental efficiency.
[0094] ②Ash analysis
[0095] The ash content of slurry bed residue oil was measured according to the ash analysis procedure (GB / T 508-1985). The average ash content of slurry bed residue oil was as high as 3426.5 μg·g -1 , which shows that the slurry bed residue contains more minerals and metal compounds, which are the key factors that deactivate the catalyst and accelerate equipment wear and corrosion.
[0096] ③Infrared spectrum
[0097] Infrared spectrum of slurry bed residue oil Figure 2 As shown, at 3400-3450cm -1 The absorption peak at 3010-3100cm is mainly due to the stretching vibration of hydroxyl OH. -1 The absorption peak is the stretching vibration of C=CH on the benzene ring, 2800-2920cm -1 The absorption peak at 1452 cm is mainly due to the stretching vibration of CH on saturated carbon. -1 、1368cm -1 The in-plane bending vibration of CH on the saturated carbon is 806 cm -1 、749cm -1 The absorption peak at is the out-of-plane bending vibration of CH on the disubstituted meta-benzene ring. The results show that the slurry bed residue contains hydroxyl and aromatic groups.
[0098] ④ The slurry bed residue oil was analyzed for four components. The results are shown in Table 1.
[0099] Table 1 Data of four components of slurry bed residue
[0100]
[0101]
[0102] The results show that the contents of the components in the slurry bed residue are aromatics, colloids, asphaltene, and saturates from high to low. This indicates that the slurry bed residue contains a large number of aromatic hydrocarbon compounds, which is consistent with the results of nuclear magnetic resonance hydrogen spectrum. These compounds have high molecular structure stability and thermal stability, and are not easily removed by simple refining processes.
[0103] ⑤X-ray fluorescence analysis
[0104] According to the X-ray fluorescence analysis procedure (GB / T 17040-2008), the content of each element in the slurry bed residue was measured. The results are shown in Table 2.
[0105] Table 2 Slurry bed residue X-ray fluorescence analysis data
[0106] element <![CDATA[Result / μg·g -1 > S 80325 V 1285 Mo 1089 Ni 634 Ag 209 Fe 119 Cu 82
[0107] The results show that the contents of the main elements in the slurry bed residue are S, V, Mo, Ni, Ag, Fe, and Cu. Among them, the contents of vanadium (V), molybdenum (Mo), and nickel (Ni) are relatively high, and the removal of these three metal elements is the research focus of optimizing the performance of the residue. Therefore, the present invention mainly studies the removal rates of vanadium, molybdenum, and nickel.
[0108] (2) Characterization of Camellia oleifera shell
[0109] ① Component analysis
[0110] The oil-tea camellia shell contains 31.4% lignin, 21.82% hemicellulose, 17.2% cellulose, 11.36% moisture, 9.76% tea saponin, 1.92% ash, and 6.54% other components. The insoluble cellulose content in the oil-tea camellia shell is as high as 70%, which has great research significance and utilization value.
[0111] ②Infrared analysis of oil-tea camellia shell
[0112] Infrared spectrum of camellia oleifera shell Figure 3 As shown, at 3440-3450cm -1 The strong absorption peaks are mainly due to the stretching vibration of OH in alcohol and phenol, 2900-3000cm -1 The absorption peak at 1725cm is the CH stretching vibration of methyl, methylene and methine. -1 Nearby and 1600-1650cm -1 The absorption peak at 1000-1050cm is mainly due to carbonyl C=O stretching vibration. -1 The absorption peak at is mainly the stretching vibration of CO. In the residual oil vacuum-heat extraction experiment, the addition of camellia oleifera shell is mainly to utilize the characteristics of its oxygen-containing functional groups (-OH, -C=O) that can form non-covalent bonds with asphaltene to remove heavy metals in the slurry bed residual oil.
[0113] ③ Electron microscopic analysis of camellia oleifera shell
[0114] Through electron microscopic analysis, the internal morphology of the oil tea shell is as follows Figure 4 As shown, it can be clearly observed that there are wrinkles and pores in the structure of the oil-tea camellia shell, which has a high specific surface area. The structural characteristics of the oil-tea camellia shell are very similar to those of walnut shells, and have similar applications and adsorption functions as other porous biomass materials.
[0115] (3) The basic properties of the filter cake were characterized. The results are shown in Table 3. The appearance of the biomass filter material and the filter cake is shown in Figure 5 .
[0116] Table 3 Basic properties of filter cake
[0117]
[0118]
[0119] Test Example 2
[0120] (1) Effect of diluent
[0121] ① The influence of different diesel on filtration time and filter cake weight, such as Figure 6 shown.
[0122] Depend on Figure 6 It can be seen that from the perspective of filtration time, it can be clearly observed that the longest time for distilled diesel is 40.25 minutes, the shortest time for RDS diesel is 7.48 minutes, and the catalytic diesel is in the middle at 25.5 minutes. This shows that RDS diesel is beneficial to reduce the viscosity of the slurry bed residue oil, thereby shortening the filtration time. Considering the weight of the filter cake, the heaviest filter cake obtained using distilled diesel diluent is 7.55g. This shows that distilled diesel is not easy to dissolve with asphaltene, so the filter material adsorbs more asphaltene. The weight of the filter cake obtained using catalytic diesel and RDS diesel is similar, which are 5.38g and 5.18g respectively.
[0123] ② The effect of different diesel fuels on the removal of vanadium, nickel and molybdenum from residual oil, such as Figure 7 Shown
[0124] Depend on Figure 7It can be seen that the removal rates of metal vanadium, molybdenum and nickel are all on a downward trend. This shows that the solubility of distilled diesel, catalytic diesel and RDS diesel on asphaltene is gradually enhanced. Distilled diesel is not easy to dissolve in asphaltene, so it can better remove vanadium and nickel from slurry bed residual oil. RDS diesel has a strong ability to dissolve asphaltene, so the removal rates of metal vanadium and nickel are relatively low. Since metal molybdenum mainly exists in the residual oil in the form of solid molybdenum sulfide, only a small part exists in asphaltene. Therefore, the solubility of various diesels in asphaltene has little effect on the removal of metal molybdenum, so that the removal rate of metal molybdenum will be higher than the removal rate of metal vanadium and nickel.
[0125] Considering the filter cake weight and metal removal rate, the performance of using distilled diesel as a diluent is better. However, combined with the actual experimental situation, considering that distilled diesel takes a long time in the filtration process, and RDS diesel has a poor metal removal effect, this experiment selected catalytic diesel with medium performance as a diluent for subsequent experimental operations.
[0126] (2) Influence of diluent mass ratio
[0127] ① The influence of different residual oil and diesel mass ratio on filtration time and filter cake weight, such as Figure 8 shown.
[0128] Depend on Figure 8 It can be seen that as the diesel content increases, the filtration time gradually decreases. This means that the higher the diesel content, the lower the viscosity of the mixed residual oil, which is conducive to the hot filtration process and can greatly shorten the filtration time. At the same time, the higher the diesel content, the more asphaltene can be dissolved, the amount of asphaltene adsorbed by the filter material will gradually decrease, and the weight of the filter cake will also decrease. However, when the mass ratio is 4:1, 3:1, and 2:1, the weight of the filter cake is similar, indicating that when the diesel reaches a certain amount, the dissolved asphaltene reaches saturation, and the effect on the weight of the filter cake is not significant.
[0129] ② The effect of different residual oil and diesel mass ratios on the removal of vanadium, molybdenum and nickel from residual oil, such as Fig. 9 shown.
[0130] Depend on Fig. 9 It can be seen that the removal rates of vanadium, molybdenum and nickel are all on a downward trend, indicating that the higher the content of diesel in the mixed residual oil, the worse the effect of metal removal. In order to reduce the consumption of raw materials, the quality ratio with less diesel content can be given priority.
[0131] After comprehensive consideration, solutions with mass ratios of 6:1, 5:1, and 4:1 had better metal removal effects. In order to reduce time consumption, the mass ratio of 4:1, which took less time, was selected as the mass ratio for subsequent operations in the experiment.
[0132] (3) Effect of the amount of camellia oleifera shell filter material added
[0133] ① The effect of the amount of camellia oleifera shell added on the filtration time and filter cake weight, such as Fig.10 shown.
[0134] Depend on Fig.10 It can be seen that the filtration time without adding camellia oleifera shells is 34.49 minutes, which is a long time consumption. The weight of the filter cake is 3.10g, and the asphaltene content in the filter cake is less. When the amount of camellia oleifera shell added is 2g, the filtration time is 17.16min and the weight of the filter cake is 4.86g. Compared with not adding camellia oleifera shells, the filtration time is shortened by 54% and the weight of the filter cake is increased by 36%. This shows that after the camellia oleifera shells adsorb asphaltene, the viscosity of the solution is reduced, which is beneficial to the hot filtration process and also improves the demetallization efficiency. With the increase in the amount of camellia oleifera shells added, the weight of the filter cake also increases, indicating that the more camellia oleifera shells are added, the more conducive to the adsorption of asphaltene.
[0135] ② The effect of tea oil shell addition on the removal of vanadium, molybdenum and nickel from residual oil, such as Fig.11 shown.
[0136] Depend on Fig.11 It can be seen that when the amount of camellia oleifera shell added is ≤2g, the removal rate of each metal increases significantly. This means that as the amount of camellia oleifera shell added increases, the oxygen-containing functional groups participating in the reaction also increase, and more asphaltene can be adsorbed, thereby increasing the removal rates of metal vanadium, molybdenum, and nickel in the residual oil. When the amount of camellia oleifera shell added is ≥2g, the increase in the removal rates of vanadium and nickel is small, while the removal rate of molybdenum tends to be stable. This is mainly because when the amount of camellia oleifera shell added is 2g, the filter cake layer formed after the camellia oleifera shell adsorbs asphaltene can intercept metal molybdenum to the greatest extent, so that after adding filter material, the removal rate of metal molybdenum does not change significantly.
[0137] Comprehensively considered, the demetallization performance is better when the amount of camellia shell added is between 2g and 4g. When the amount of camellia shell added exceeds 2g, the filtration time becomes longer. In order to reduce time consumption, the appropriate amount of camellia shell added is determined to be 2g, and it is used as the amount of camellia shell added in subsequent operations.
[0138] (4) Influence of filtration temperature
[0139] ① The influence of filtration temperature on filtration time and filter cake weight, such as Fig.12 shown.
[0140] Depend on Fig.12It can be seen that when the temperature is 100℃, the filtration time is the longest, which is 55.28min; the filter cake weight is the heaviest, which is 6.55g. When the temperature is 140℃, the filtration time is the shortest, which is 25.32min; the filter cake weight is the lightest, which is 4.77g. This shows that as the temperature rises, the viscosity of the mixed residual oil will gradually decrease, and the filtration time can be shortened by about 50%, which is beneficial to the filtration process. On the whole, as the temperature increases, the filtration time and the weight of the filter cake both decrease. This shows that the higher the temperature, the lower the force between the asphaltene adsorbed by the oil tea shell filter material. The longer the filtration time, the more it will affect the time cost and energy consumption of the experiment. The experiment will give priority to the filtration temperature with a shorter filtration time.
[0141] ②The effect of filtration temperature on the removal of vanadium, molybdenum and nickel from residual oil, such as Fig.13 shown.
[0142] Depend on Fig.13 It can be seen that with the increase of temperature, the removal rate of vanadium and nickel decreases. This shows that the increase of temperature will intensify the thermal motion of molecules in the residual oil, leading to the depolymerization of asphaltene, thereby reducing the adsorption between the filter material and asphaltene, and reducing the removal rate of vanadium and nickel. When the temperature is between 100℃ and 120℃, the removal of molybdenum first increases slightly. After exceeding 120℃, the removal rate of molybdenum decreases slightly, fluctuating roughly between 92% and 94%. This is mainly because metallic molybdenum exists in the residual oil in the form of solid sulfide, and only a small part exists in asphaltene, so the temperature has little effect on the removal rate of molybdenum.
[0143] After comprehensive consideration, this experiment selected 130℃ as the appropriate filtration temperature while giving priority to time cost and energy consumption.
[0144] (5) Filter cake roasting process
[0145] During the roasting process, the non-metallic components in the residue should be removed as thoroughly as possible. Controlling the roasting temperature is an important factor in this process. On the one hand, too high a temperature can easily lead to metal volatilization; on the other hand, too low a temperature may affect the subsequent alkali solution leaching.
[0146] In order to study the pyrolysis law of filter cake, thermogravimetric analysis was carried out on two filter cakes (biomass-filter cake and blank-filter cake), and TG-DTG curves were obtained under air environment at a heating rate of 15℃ / min. Fig.14 are the TG and DTG curves of the two filter cakes. Fig.14(a) It can be seen that both filter cakes are gradually pyrolyzed, and the process of heating from 0℃ to 900℃ can be divided into three stages: the first stage is 0-430℃, and the filter cake mass loss is relatively slow. This phenomenon may be due to the high concentration of asphaltene and colloids, as well as some light components in the filter cake. In this stage, the thermal decomposition of asphaltene and colloids is not significant, while the light components tend to decompose into small molecules. In addition, the C=O bond energy in the filter cake is relatively weak and easy to break, generating CO2 or CO, which causes the mass reduction rate to remain at a low level. The second stage is the pyrolysis of the filter cake, mainly at 450-750℃, with a large mass loss. This stage involves complex thermal conversion reactions, which are based on free radical mechanisms, including the breakage of CC bonds, CH bonds in hydrocarbons and C-heteroatom (such as S, N, O) bonds in non-hydrocarbons. In addition, it also includes side chain breakage, dehydrogenation and ring opening reactions of cycloalkanes, and dehydrogenation and condensation reactions of aromatics. The third stage is after 700-750℃, the TG and DTG curves tend to be stable, the pyrolysis of the filter cake is basically completed, and the final ash components are mainly coke and metal oxides. Fig.14 (a) It can be found that the TG curve of biomass-filter cake reaches stability faster than that of filter cake without filter material, and burns more completely. First, adding biomass filter material can provide heat, which helps the filter cake burn and make it reach stability faster. Second, adding biomass filter material can change the aggregation state of asphaltene. Adding biomass filter material can make the originally compact asphaltene more dispersed, allowing oxygen to enter better during combustion, making the filter cake burn more cleanly.
[0147] (2) Effect of calcination time on filter cake loss
[0148] Depend on Fig.15 It can be seen that the quality of biomass-filter cake and blank-filter cake tends to be stable after 6 hours, but the burning loss rate of biomass-filter cake is always higher than that of blank-filter cake at the same time. When roasted for 6 hours, the burning loss rate of biomass-filter cake is 98.01%, and the burning loss rate of blank-filter cake is 95.26%. After 6 hours, the burning loss rate of both filter cakes changes very little, so the filter cake is roasted after 6 hours, and the roasting performance of biomass-filter cake is more superior.
[0149] (3) Effect of roasting time on metal leaching rate
[0150] The leaching time was 2h, 4h, 6h, 8h and 10h respectively. Fig.16 shown.
[0151] Depend on Fig.16It can be seen that the leaching rates of metal molybdenum and vanadium in the roasted product increase with the increase of roasting time. When the roasting time is 2h, the leaching rate of metal vanadium is 43.48%, and the leaching rate of molybdenum is 33.89%; as the roasting time increases to 6h, the leaching rate of vanadium is 80.37%, and the leaching rate of molybdenum is 51.21%. The metal leaching rate increases with the increase of roasting time. This trend may be because, under a shorter roasting time, the non-metallic components in the filter cake are not completely removed, thereby limiting the effective dissolution of metal molybdenum and vanadium. Continue to extend the roasting time to 10h, the leaching rate of vanadium is 86.62%, and the leaching rate of molybdenum is 88.87%. At this time, since the filter cake is fully roasted, the non-metallic group in the filter cake can be completely removed, and the metal leaching rate continues to increase. For metallic vanadium roasted for 6 hours, increasing the roasting time has limited effect on increasing the leaching rate. Although the leaching rate of metallic molybdenum is low at 6 hours, if the loss on ignition rate factor is taken into account, continuing to extend the roasting time will result in a small change in the loss on ignition rate, which will lead to energy consumption. The molybdenum leaching rate can be subsequently increased by extending the leaching time. Therefore, the optimal roasting time is selected as 6 hours.
[0152] (4) Effect of different immersion temperatures on metal leaching rate
[0153] When the soaking time is 120min, the influence of soaking temperature is investigated, and the soaking temperatures are set to 50℃, 60℃, 70℃, 80℃ and 90℃ respectively. The influence of soaking temperature on the leaching rate of vanadium and molybdenum is as follows Fig.17 shown.
[0154] Depend on Fig.17 It can be seen that with the increase of soaking temperature, the vanadium leaching rate increases significantly. At 50 ° C, the vanadium leaching rate is 51.81%; when the temperature rises to 80 ° C, the yield increases significantly to 86.22%; until 90 ° C, the leaching rate reaches the highest, which is 86.44%. The molybdenum leaching rate also increases with the increase of soaking temperature. At 50 ° C, the molybdenum leaching rate is 69.08%; when the temperature rises to 80 ° C, the molybdenum yield reaches the highest, which is 94.09%; and when it rises to 90 ° C, the molybdenum leaching rate drops slightly to 92.99%. The metal leaching rate increases with the increase of soaking temperature. This trend may be because the increase in temperature can intensify the Brownian motion of molecules, increase the frequency of collisions between molecules, accelerate the dissolution rate of metal vanadium and molybdenum, and increase the leaching rate of metal vanadium and molybdenum. Since the metal leaching rate does not change much when the soaking temperature continues to increase, the optimal soaking temperature is selected as 80 ° C.
[0155] (5) Effect of different immersion times on metal leaching rate
[0156] At an immersion temperature of 80°C, the effect of immersion time was investigated, and the immersion time was set to 30 min, 60 min, 90 min, 120 min and 150 min respectively. The effect of immersion time on metal leaching rate is as follows Fig.18 shown.
[0157] Depend on Fig.18 It can be seen that the vanadium leaching rate increases with the increase of immersion time. At 30 minutes, the vanadium leaching rate is 76.71%; when the immersion time is 60, 90, and 120 minutes, the increase is small; when the immersion time reaches 150 minutes, the vanadium yield rises sharply to 88.24%. The molybdenum leaching rate also increases with the increase of immersion time. At 30 minutes, the molybdenum leaching rate is 77.46%; when the time is 150 minutes, the molybdenum leaching rate reaches the highest, which is 90.99%. Since it takes a long immersion time to reach the highest metal leaching rate, when the immersion time is 120 minutes, the vanadium leaching rate is 81.72%, and the molybdenum leaching rate is 88.13%. Compared with the immersion time of 150 minutes, the time is reduced, and the leaching rate is less different. The leaching rates of metal vanadium and molybdenum increase with the increase of immersion temperature, which may be because the immersion time is long and the reaction is sufficient, which accelerates the dissolution rate of metal vanadium and molybdenum, resulting in an increase in the leaching rate of metal vanadium and molybdenum. As the immersion time continued to increase, the leaching rates of metal vanadium and molybdenum remained similar. Therefore, the optimal immersion time was selected as 120 minutes.
[0158] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for extracting heavy metals from slurry bed hydrogenation residue oil, characterized in that: The following steps are involved: (1) mixing the residual oil and the diluent and heating and melting them to obtain a mixed residual oil; (2) After washing, drying and crushing the natural biomass, a biomass filter material is obtained; (3) mixing and stirring the mixed residual oil and the biomass filter material, and then performing vacuum-hot filtration while hot to obtain a filter cake and a first filtrate; (4) calcining the filter cake to obtain a sintered product; (5) Immersing the sintered product in an alkaline solution, and then filtering to obtain an alkaline leaching solution and a filter residue; (6) adding an acidic solution 1 to the filter residue to dissolve it, then filtering it to obtain a second filtrate, adding an alkaline solution 2 to the second filtrate to precipitate it, then filtering it to obtain a nickel hydroxide precipitate, and sintering the nickel hydroxide precipitate to obtain a nickel oxide product; (7) adding ammonium salt to the alkaline leaching solution to promote the formation of precipitation between ammonium ions and vanadium ions in the alkaline leaching solution, followed by filtration to obtain vanadium precipitate and a third filtrate, and sintering the vanadium precipitate to obtain a V2O5 product; (8) Add acidic solution 2 to the third filtrate to promote MoO4 2- With H + A reaction occurs to generate H2MoO4 precipitate, which is then filtered to obtain molybdenum precipitate, and the molybdenum precipitate is calcined to obtain MoO3 product.
2. The method for extracting heavy metals from slurry bed hydrogenated residual oil according to claim 1, characterized in that: In step (1), the diluent includes one or more of distilled diesel, catalytic diesel, and RDS diesel; the mass ratio of residual oil to diluent is (2-6):1; the heating temperature is 125-135°C, and the heating time is 10-20 minutes.
3. The method for extracting heavy metals from slurry bed hydrogenated residual oil according to claim 1, characterized in that: In step (2), the natural biomass is camellia oleifera shell, and the particle size of the biomass filter material is 50-200 mesh.
4. The method for extracting heavy metals from slurry bed hydrogenated residual oil according to claim 1, characterized in that: In step (3), the amount of biomass filter material added is 0.5-4% of the mass of the mixed residual oil, the mixing temperature is 100-140°C, and the time is 10-20 minutes.
5. The method for extracting heavy metals from slurry bed hydrogenated residue according to claim 1, characterized in that: In step (4), the calcination temperature is 500-800°C and the calcination time is 4-10 hours.
6. The method for extracting heavy metals from slurry bed hydrogenated residual oil according to claim 1, characterized in that: In step (5), the alkaline solution 1 includes one or more of sodium hydroxide, sodium bicarbonate, sodium carbonate, and potassium hydroxide solution; the concentration of the alkaline solution 1 is 0.5-2 mol / L; the solid-liquid ratio of the sintered product and the alkaline solution 1 is (5-15) mL:1 g; the immersion temperature is 60-100° C., and the immersion time is 60-150 min.
7. The method for extracting heavy metals from slurry bed hydrogenated residual oil according to claim 1, characterized in that: In step (6), the first acidic solution is hydrochloric acid, the second alkaline solution is sodium hydroxide, the precipitation temperature is 50-90° C., and the precipitation time is 1-3 h.
8. The method for extracting heavy metals from slurry bed hydrogenated residue according to claim 1, characterized in that: In step (7), the ammonium salt is an ammonium chloride solution, the precipitation temperature is 50-90°C, and the precipitation time is 1-3 hours.
9. The method for extracting heavy metals from slurry bed hydrogenated residue according to claim 1, characterized in that: In step (8), the second acidic solution is one or more of sulfuric acid, hydrochloric acid, and nitric acid; the precipitation temperature is 50-90° C., and the precipitation time is 1-3 h.
Citation Information
Cited By
Residual oil resource utilization device and system method
CN122405321A
A device and system method for resource utilization of residual oil
CN122405321B